2006
DOI: 10.1016/j.jbankfin.2006.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the effects of financial liberalization: Crises vs. growth

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 17 publications
(30 reference statements)
5
114
3
2
Order By: Relevance
“…There is an ongoing debate on whether financial globalization has helped emerging markets expand and boost investment (Bekaert et al, 2016). Some studies argue that liberalization has alleviated financial constraints and decreased the cost of capital, thereby boosting investment, growth, and productivity (Bekaert et al, 2005(Bekaert et al, , 2011Bonfiglioli, 2008;Chari & Henry, 2008;Gupta & Yuan, 2009;Henry, 2000a;Laeven, 2003;Larrain & Stumpner, 2017;Ranciere, Tornell, & Westermann, 2006). However, other studies have found no systematic investment and growth bonus linked to increasing the level of foreign ownership in emerging markets (Aizenman et al, 2007;Singh & Weisse, 1998;Stiglitz, 2000), with financial integration linked to increases in consumption volatility (Kose, Rogoff, Prasad, & Wei, 2003).…”
Section: Integration and Real Economic Activitymentioning
confidence: 99%
“…There is an ongoing debate on whether financial globalization has helped emerging markets expand and boost investment (Bekaert et al, 2016). Some studies argue that liberalization has alleviated financial constraints and decreased the cost of capital, thereby boosting investment, growth, and productivity (Bekaert et al, 2005(Bekaert et al, , 2011Bonfiglioli, 2008;Chari & Henry, 2008;Gupta & Yuan, 2009;Henry, 2000a;Laeven, 2003;Larrain & Stumpner, 2017;Ranciere, Tornell, & Westermann, 2006). However, other studies have found no systematic investment and growth bonus linked to increasing the level of foreign ownership in emerging markets (Aizenman et al, 2007;Singh & Weisse, 1998;Stiglitz, 2000), with financial integration linked to increases in consumption volatility (Kose, Rogoff, Prasad, & Wei, 2003).…”
Section: Integration and Real Economic Activitymentioning
confidence: 99%
“…Wang Dongjing and Zhang Xiangjian (2007) [26] believe that the loan interest rate rises after easing the government's control of interest rates, which will increase the financing cost of the enterprise, and restrain the excessive capital demand of the enterprise, so that it will alleviate the problem of credit rationing. The research of Ranciere R., Tornell A., and Westermann F. (2006) [27] shows that interest rate marketization will be beneficial to the financing and economic growth of the small-and medium-sized enterprises. Li Cheng, Huang Youxi, and Li Yuliang (2014) [24] hold that interest rate marketization is able to improve the financing difficulty of non-state-owned enterprises, to help to reduce the gap in the return on loans between the state-owned enterprises and non-state-owned enterprises, and to improve the loan incentives of banks to the non-state economy, and they adopted the panel data of 39 industries from 2002 to 2011 to test the correctness of the theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, some countries have actively promoted the development of local stock markets and encouraged entry of foreign financial intermediaries. These liberalization measures have shown increased economic growth in empirical studies (see Bekaert, Harvey, & Lundblad, 2005;Klein & Olivei, 2008;Quinn & Toyoda, 2008;Ranciere, Tornell, & Westermann, 2006).…”
Section: Financial Liberalization and Banking Crisismentioning
confidence: 99%